2007
DOI: 10.1159/000104167
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Can Elicit The Recurrence of Gastric Ulcer Induced with Acetic Acid in Rats

Abstract: This study was supported by grants of New Ideas Capability for Backbone Teachers in Universities of Heilongjiang and of Scientific Research foundation in Qiqihar Medical College. Background/ Aims: Ulcer recurrence and poor healing may be critically important to the development of serious gastrointestinal complications in patients with long-term non-steroid anti-inflammatory drugs (NSAIDs). The present study is to investigate the effects of aspirin on ulcer recurrence and healing quality and to explore the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 36 publications
(30 reference statements)
1
23
0
Order By: Relevance
“…nitroglycerin protects against acidified aspirin-induced gastric mucosal injury in mice [88]. One recent study demonstrated that aspirin enhance the recurrence of gastric ulcer induced by acetic acid [89], suggesting that the acetic acid gastric ulcer model is suitable for assessing the effect of nitroglycerin on the enhancement of ulcer recurrence by aspirin.…”
Section: Nitroglycerin and Aspirin-induced Gastric Injurymentioning
confidence: 99%
“…nitroglycerin protects against acidified aspirin-induced gastric mucosal injury in mice [88]. One recent study demonstrated that aspirin enhance the recurrence of gastric ulcer induced by acetic acid [89], suggesting that the acetic acid gastric ulcer model is suitable for assessing the effect of nitroglycerin on the enhancement of ulcer recurrence by aspirin.…”
Section: Nitroglycerin and Aspirin-induced Gastric Injurymentioning
confidence: 99%
“…At low expression levels of SGK1, as in the absence of glucocorticoids, the inhibitory effect appears to prevail. Beyond their effect on SGK1, glucocorticoids downregulate cycloxygenase [36,37], an effect similarly expected to enhance gastric acid secretion [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…SGK1 has been shown to upregulate a wide variety of channels and transporters [43], including KCNQ1 [44][45][46]. Glucocorticoids exert further effects in gastric glands, such as the downregulation of cyclooxygenase [47,48], which is known to enhance gastric acid secretion [47][48][49][50]. At least in theory, these additional effects of glucocorticoids may modify PI3-kinase-dependent regulation of gastric acid secretion.…”
Section: Discussionmentioning
confidence: 99%